New antiepileptic drugs in intractable seizures in childhood - Karabiber, Hamza; Yakinci, Cengiz; Sahin, Sabit (Annals of Medical Research, 2021)
None
Keywords: Intractable seizures, Felbamate. Gabapentin, Lamotrigine, Vigahatrin